Evaluation of patient care cascade for HIV-positive patients diagnosed in La Romana, Dominican Republic in 2011: a retrospective cohort study. (April 2016) - Bowman, Alex S; Lerebours, Leonel; Amesty, Silvia; de la Rosa, Milagros; Gil, Elizabeth; Halpern, Mina; Nicholas, Stephen; Lamb, Matthew R
The Caribbean has the highest adult HIV prevalence in the world after sub-Saharan Africa (2011). One sub-population in the Dominican Republic is the migratory Batey community primarily comprised of Haitian immigrants with limited access to healthcare and HIV prevalence rates of between 3.0% and 9.0%, compared to 0.7% nationally. This retrospective cohort study describes the cumulative retention from diagnosis to virological suppression for newly-diagnosed HIV-infected adults presenting to the Clínica de Familia and its Batey programme in La Romana, during 2011. Of the patients diagnosed with HIV, 65% entered into care, 59% completed immunologic testing, 53% were eligible for antiretroviral therapy (ART) initiation, 36% initiated ART within three months of eligibility and 27% were retained in care. Seventeen per cent of those retained on ART with a 12-month viral load measure had undetectable viral load. Attrition primarily occurred before ART initiation. The Batey programme had a first step lost-to-follow-up of 88% compared to 20% at the clinic ( p  < 0.001). This retrospective study details the continuum of care and indicates where structural changes must occur to increase continuity between steps. The manuscript results are important to help implement programmes to enhance engagement and retention in HIV primary care.